MORPHOPHYSIOLOGICAL CHARACTERIZATION IN SUGARCANE MINI SETTS AS A FUNCTION OF AGE, POSITION IN THE STALK AND AIR TEMPERATURE - Kleber Romani, Grace Karina; Zanatta, Marcela Maria; Aparecida Oliarski, Anabel; Wagner, Lucas; Bespalhok Filho, João Carlos; Portela Brasileiro, Bruno (Scientia Agraria, 2025)
This study evaluated the morphophysiological characteristics of sugarcane buds from different stalk positions of the Havaianinha variety under varying air temperatures, aiming to understand biotic and abiotic factors affecting seedling production via the pre-sprouted seedling (PSS) system. Two experiments were conducted at the Micropropagation Laboratory of the Federal University of Paraná, using a completely randomized design (CRD) in a 4 × 3 factorial scheme (four temperature levels: 15, 20, 25, and 30 ºC; three bud positions: apical, median, and basal) with three replications. Each experimental unit contained 20 mini setts. The sprouting speed index (SSI), sprouting percentage (SP), and sprouting height (SH) were evaluated. Data were analyzed using ANOVA, Pearson correlation, Scott-Knott test (5%), and regression analysis for temperature. SSI, SP, and SH were influenced by mini sett age, temperature, and bud position. The highest values for all parameters occurred at 30 ºC, using apical buds from 18-month-old culms or buds from any position on 6-month-old culms. Temperatures below 20 ºC negatively affected all variables. Positive correlations among SSI, SP, and SH were observed. For optimal PSS seedling production, younger culms should be used to maximize bud utilization.